Prevalence of Intestinal Parasites and Gastrointestinal Carriage of Pathogenic Gram Negative Enteric Bacteria among Apparently Healthy Food Handlers of Public Hospitals, Addis Ababa, Ethiopia - Tegegn Belhu; Kinfe Fissehatsion; Abraham Tesfaye; Dr Yohannes Woldekidan; Kassu Desta (International Journal of Microbiology)
Background. Foodborne diseases are major public health problems in developing countries like Ethiopia. Food handlers with poor personal hygiene working in hospitals could be infected with different intestinal parasites and pathogenic enteric bacteria. Therefore, they could pose a potential risk of foodborne infection to patients and the community. Methods. An institutional based cross-sectional study conducted from March to June 2017. Besides, sociodemographic data were collected using a structured questionnaire, freshly passed stool specimens for direct wet mount smear examination, and formalin ether concentration techniques performed for the detection of parasites. For bacterial identification culture, biochemical tests and antimicrobial sensitivity (Kirby-Baure disk diffusion method) have been performed. Finally, validated data were analyzed using statistical package for social science version 20 (SPSS). Results. From 368 food handlers who participated in the study, 81% were females. 119 (32.34%) were positive for at least one intestinal parasite. The most prevalent parasite was Entamoeba histolytica/dispar 48 (13%), followed by Giardia lamblia 36 (9.78%), Taenia Species 21 (5.7%), Ascaris lumbricoide 8 (2.2%), Trichuris trichiura 5 (1.4%), and Hook worm 1 (0.3%). Regarding the prevalence of enteric bacteria 17(4.6%), food handlers were positive for Salmonella 14 (3.8%) and Shigella flexneri 3 (0.8%). No E. coli O157 : H7 was isolated. All 100% (n = 14) Salmonella isolates were resistant to ampicillin (10 µg) and erythromycin (15 µg). Similarly, 100% (n = 3) of Shigella flexneri isolates were resistant to ampicillin (10 µg) and tetracycline (30 µg). 14.3% (n = 2) Salmonella and 66.7% (n = 2) Shigella flexneri isolates were MDR. Conclusion. The study showed significant carriage of pathogenic microorganisms among food handlers. Therefore, hospital administrators and other stake holders should put measures in place to break chain of transmission routes from silent carrier to other peoples particularly patients at hospital and the community at large.